Upaya Meningkatkan Hasil Belajar Bahasa Inggris Materi Menulis Procedure Text melalui Penerapan Metode Demonstrasi pada Siswa Kelas X TDPIB -1 SMK Negeri 2 Karang Baru Aceh Tamiang - Sri Afrila Yanti (Medan Resource Center, 2022)
The purpose of this study is: To Improve English Learning Outcomes Writing Materials for Procedure Text in Class X TDPIB-1 Students of SMK Negeri 2 Karang Baru Aceh Tamiang Regency Through the Application of the Demonstration Method. This study used two rounds of action research. Each round consists of four stages: design, activity, observation, and reflection. The target of this study were students of Class X TDPIB-1 at SMK Negeri 2 Karang Baru, Aceh Tamiang Regency. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I first meeting to cycle II second meeting namely, cycle I the first meeting 45%, cycle I the second meeting 65%, and cycle II the first meeting 75%, cycle II the second meeting 90% , classically students achieve mastery of learning outcomes. The conclusions from this research are: Through the Application of the Demonstration Method it can improve English Learning Outcomes of Procedure Text Writing Material for Class X TDPIB-1 Students of SMK Negeri 2 Karang Baru Aceh Tamiang Regency. These results can be seen from the increase in learning, namely the first cycle at the first meeting 45% and the second meeting 65% of the second cycle of the first meeting 75% and the second meeting 90% (classical complete).